Global myocardial strain after the Ozaki aortic valve replacement in low-gradient critical aortic stenosis and heart failure: a case report - E. V. Rosseikin; E. N. Pavlyukova; V. I. Skidan; E. E. Kobzev; I. D. Potopalsky (Российский кардиологический журнал)
The article presents the results of 1,5-year follow-up after surgery of critical aortic stenosis by the Ozaki technique in a patient with severe heart failure using data on global longitudinal strain.